Analysis of the Quality of Bojonegoro Police Traffic Services in Making Driving Licenses (SIM) and the Existence of SIM Brokers in Bojonegoro - Adelia, Evi; Wulandari, Septi; Junadi, Junadi (Riwayat: Educational Journal of History and Humanities, 2025)
Research on Analysis of the Quality of Services for Making Driver's Licenses (SIM) at the Bojonegoro Police Station and the Existence of Driver's License Brokers. Qualitative methods with interview and field observation techniques are used, and this study uses five indicators of service quality according to Parasuraman, namely realism, responsiveness, assurance, empathy, and tangibles. The results of this study show that the SIM-making service at the Bojonegoro Police Station is adequate. Especially in terms of clarity of information, professionalism of officers, and transparency of costs. Regarding the existence of SIM Brokers in Bojonegoro, they have been successfully suppressed through strict supervision and strict sanctions against the individuals involved. However, several obstacles, such as long queues due to a manual system and the lack of digital services, are still challenges.